Urban water supply and sanitation - World Bank (Washington World Bank, 1999)
Urban water supply and sanitation is a World Bank Publication. This reports recommended strategy aims at transforming the current vicious circle and focuses on improving the incentives faced by UWSS instutions through appropriate democratic governance. Th
Keywords: Municipal water supply-Economic aspects-India; Sewage disposal-Economic aspects-India; Sanitary engineering-India-Planning; Rural development-India